2020
DOI: 10.3174/ajnr.a6447
|View full text |Cite
|
Sign up to set email alerts
|

The FRED for Cerebral Aneurysms of the Posterior Circulation: A Subgroup Analysis of the EuFRED Registry

Abstract: BACKGROUND AND PURPOSE: Flow diversion for the posterior circulation remains a promising treatment option for selected posterior circulation aneurysms. The Flow-Redirection Intraluminal Device (FRED) system has not been previously assessed in a large cohort of patients with posterior circulation aneurysms. The purpose of the present study was to assess safety and efficacy of FRED in this location. MATERIALS AND METHODS:Consecutive patients with posterior circulation aneurysms treated at 8 centers participating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…25 Few studies have explored the use of flow diversion in the posterior circulation. Grissenauer et al 21 performed a subgroup analysis of the European FRED (EuFRED) study 13 of patients treated with the FRED for posterior circulation aneurysms. Complete occlusion at last follow up was 78.2%, which is comparable to occlusion rates seen in the studies presented in this review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Few studies have explored the use of flow diversion in the posterior circulation. Grissenauer et al 21 performed a subgroup analysis of the European FRED (EuFRED) study 13 of patients treated with the FRED for posterior circulation aneurysms. Complete occlusion at last follow up was 78.2%, which is comparable to occlusion rates seen in the studies presented in this review.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two studies published between January 1, 2013 and April 30, 2021 are included in this review. [1][2][3][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] One study published results in 2 separate papers. 2,3 Table 1 outlines the characteristics of each study.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The most common aneurysm type was saccular and favorable safety results were shown, but thromboembolic complications were more frequent in non-saccular aneurysms. 21) The therapeutic results of mid/distal-basilar and holobasilar aneurysm involving AICA showed the worst neurological outcome. 22) Conversely, if holobasilar aneurysms or aneurysms with a large amount of thrombus were not involved, the treatment outcome was reported to be excellent.…”
Section: Discussionmentioning
confidence: 96%
“…[1][2][3] Current studies have even shown that the risk profile of such devices has decreased compared to the early years. [4][5][6][7][8][9][10] By diverting blood flow away from the aneurysm, they aim to alter the dynamics of intra-aneurysmal flow to induce thrombosis that leads to the occlusion of the aneurysm over time. This is one of the few methods in the treatment of cerebral aneurysms where complete reconstruction of the original vessel wall and thus complete healing of the parent vessel is possible.…”
Section: Introductionmentioning
confidence: 99%